The effects of work: A Simmelian view of delivery platforms - Ballestrin, Juan Bautista (2023)
Based on historical materialistic perspectives that account for certain characteristics of the work at delivery platforms, this article presents a qualitative analysis of such work, taking workers currently operating in the City of Buenos Aires as empirical reference. A Simmelian theoretical interweaving of the categories of money, freedom, vocation, acceleration and boredom is carried out to reveal some of the subjective foundations on which this type of employment is based, as well as certain adverse personal effects and affections it can cause to those who carry it out.